Using Mobile Phone Texting to Support the Capacity of School Leaders in Ghana to Practise Leadership for Learning - Swaffield, Sue; Jull, Stephen; Ampah-Mensah, Alfred (Procedia - Social and Behavioral Sciences, 2013)
Several years into a collaborative professional development programme to build the Leadership for Learning capacity of Basic school headteachers throughout Ghana, the challenge is to sustain commitment, deepen understanding and share learning among the school leaders. Employing ubiquitous mobile phone technology, weekly text messages have been sent to the programme's 175 initial participants. During the year of the pilot project different forms of messages have been tried, and feedback from recipients suggests their value. The paper reports experience and findings from the pilot, and considers plans for scaling-up to reach all 18,000 Basic schools across the country.
shortDOI: 10/gf7gsh KerkoCite.ItemAlsoKnownAs: 10.1016/j.sbspro.2013.10.459 10/gf7gsh 2339240:6QNXM9T9 2339240:C993QBLL 2405685:38U7QI2P 2405685:V3PRBKSK 2405685:XNAPWJG9 2405685:XNBYZ9E9
Keywords: Ghana; Leadership for Learning; SMS; headteachers; mobile phone; professional development; school leaders; text messages

An Investigation of the Impact of an Intervention to Reduce Academic Procrastination Using Short Message Service (SMS) Technology - Davis, D; Abbitt, J (Journal of Interactive Online Learning, 2013)
This mixed-method pilot study investigated the impact of a custom Short Message Service (SMS) reminder system developed to help students reduce procrastination and increase performance on weekly content-related quizzes in a high-enrollment hybrid online course. Text message reminders were sent to three students with high procrastination and low performance levels on a schedule based on free-operant avoidance principles, where messages would be terminated upon completion of the weekly quiz. The results suggest that there was sufficient evidence that the system had a positive effect on procrastination levels, but less evidence for an effect on performance. Subsequent interviews with the participants confirmed the utility and potential of the system, and revealed areas for improvement in the implementation of the SMS reminder system as well as an understanding of the students’ response to the intervention.
KerkoCite.ItemAlsoKnownAs: 2405685:GVZZTKW6
Keywords: ⛔ No DOI found

The Effect of Teacher-Family Communication on Student Engagement: Evidence from a Randomized Field Experiment - Kraft, M; Dougherty, Shaun (Journal of Research on Educational Effectiveness, 2013)
In this study, we evaluate the efficacy of teacher communication with parents and students as a means of increasing student engagement. We estimate the causal effect of teacher communication by conducting a randomized field experiment in which sixth- and ninth-grade students were assigned to receive a daily phone call home and a text/written message during a mandatory summer school program. We find that frequent teacher–family communication immediately increased student engagement as measured by homework completion rates, on-task behavior, and class participation. On average, teacher–family communication increased the odds that students completed their homework by 40%, decreased instances in which teachers had to redirect students’ attention to the task at hand by 25%, and increased class participation rates by 15%. Drawing upon surveys and interviews with participating teachers and students, we identify three primary mechanisms through which communication likely affected engagement: stronger teacher–student relationships, expanded parental involvement, and increased student motivation.
KerkoCite.ItemAlsoKnownAs: 10.1080/19345747.2012.743636 2339240:3H26G6RN 2339240:X9LRSMNV 2405685:7HER36AG 2405685:BXJPVKUP 2405685:WYAJLA9C 2534379:82ZR3C22
Keywords: ___working_potential_duplicate